Системный подход к мультидисциплинарной оптимизации машин - Назаренко, Сергей Александрович (НТУ "ХПИ", 2009)
Розглядаються проблемні питання, що виникають при розробці системного підходу до оптимізації моделей машин з високим ступенем геометричної і фізичної інформативності; які орієнтовані на великі розмірності векторів перемінних стану і проектування. Досліджено обчислювальні етапи. Розглянуто застосування розробленого математичного апарату.

The complex of theoretical, calculable and applied questions of new approach for the optimization of complicated technical systems are studied. The basic requirements were stated. The design principles were developed. Structural elements was distinguished. The common scheme of interaction between structural elements was elaborated. New schemes for solving formulated problems are proposed. Computational stages are investigated.
Keywords: оптимизация конструкций; мультидисциплинарная оптимизация; информативность; блочно-иерархический процесс